1990
DOI: 10.2307/1940302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Resources on Plant Invasion and Community Structure in Californian Serpentine Grassland

Abstract: Non-native annual grasses dominate most Californian mediterranean-climate grasslands today. However, native Californian grassland flora persists in grasslands on serpentine-derived soils. We manipulated soil nutrient resources to explore the links between nutrient availability, plant productivity, and the relative abundances of native and non-native species in serpentine grassland. Factorial combinations of nitrogen, phosphorus, and other components of a nutritionally complete formula were added to field plots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
557
6
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 691 publications
(618 citation statements)
references
References 34 publications
47
557
6
8
Order By: Relevance
“…In fact, the other resources, when added individually, had no eVect on invader performance. These results are consistent with those of other studies, which have shown that fertilization increases the invasibility of serpentine grasslands (Turitzin 1982;Huenneke et al 1990;O'Dell and Claassen 2006). The serpentine outcrops in this All N P H20 Ca study were not only lower in N availability, but were also drier and considerably lower in Ca and Ca:Mg ratios than soils in the surrounding matrix (e.g., Huenneke et al 1990;Harrison 1999;Gram et al 2004).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In fact, the other resources, when added individually, had no eVect on invader performance. These results are consistent with those of other studies, which have shown that fertilization increases the invasibility of serpentine grasslands (Turitzin 1982;Huenneke et al 1990;O'Dell and Claassen 2006). The serpentine outcrops in this All N P H20 Ca study were not only lower in N availability, but were also drier and considerably lower in Ca and Ca:Mg ratios than soils in the surrounding matrix (e.g., Huenneke et al 1990;Harrison 1999;Gram et al 2004).…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those of other studies, which have shown that fertilization increases the invasibility of serpentine grasslands (Turitzin 1982;Huenneke et al 1990;O'Dell and Claassen 2006). The serpentine outcrops in this All N P H20 Ca study were not only lower in N availability, but were also drier and considerably lower in Ca and Ca:Mg ratios than soils in the surrounding matrix (e.g., Huenneke et al 1990;Harrison 1999;Gram et al 2004). However, our results suggest that it is the low N, or low N in combination with other resources that primarily limits the invasion of three invasive grasses, suggesting that metal toxicity is not the primary factor limiting the invasions of these serpentine grasslands by exotic annual grasses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, an undesired effect can occur, where a fertilizer can increase competition between desirable and weedy plant species (Pyšek and Leps 1991). In some cases, fertilization has led to declines in species richness on a site, specifically native species, due to suppression of native forbs from an increase in non-native species cover (Buckley and Catford 2016;Huenneke et al 1990). Non-native species are of concern on reclamation sites since they are initially unoccupied.…”
Section: Introductionmentioning
confidence: 99%